Crime and the economy - Rosenfeld, Richard (Compact criminology, 2013)
"In the current economic climate, this book could not be more timely. One of the world's leading experts explores the connections between crime and economic conditions, linking the formal economy to the operation of illegal markets and both, in turn, to changes in the forms and levels of crime over time. The book offers a readable, interesting and accessible analysis, covering a range of theoretical and empirical approaches. It addresses a range of different criminal activities, including: violent crime ; burglary ; drug crime ; white collar crime ; organised crime ; fraud ; corporate crime. Crime and the Economy is written in plain English, technical terms (when used) are be explained clearly, examples punctuate the discussion, and visual material is used throughout to explain the topics under discussion. It is essential reading for undergraduates and graduates in criminology and sociology."--Publisher's website.